ANALISIS PENGARUH BAURAN PEMASARAN ("7P") PADA KEPUASAN DAN LOYALITAS KONSUMEN APARTEMEN FOUNTAIN PARK JAKARTA - , Ayla Dewi Anggraeni, Ike Janita Dewi, SE,MBA,Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The objective of this research is to examine the effect of the marketing mix, or better known as (7P) towards customer satisfaction and loyalty on Fountain Park Apartment, and identifying the Fountain Park Apartment positioning by comparing this apartment with 12 other apartment in the Jakarta area, especially in the central business district in South Jakarta and Central Jakarta. This research is divided by 2 mainstream research which is pre-study and main studi. The pre studi method of data collection is by interview and survey approach, and on main study is by distribution of questionnaires to 53 tenant in Fountain Park Apartment and than interview and observation towards 12 other apartements competitors. The type of the research is quantitative and qualitative descriptive or mix method. The model of data analysis used in pre study is precentation scooring, and for the main study is multiple linear regression, simple linear regression and multidimential scale to draw the positioning map matrix. The result of research indicates that variables of people, price, and promotion, have postive significant effect to the customersâ satisfaction, and customerâs satisfaction have positive significant effect with customerâs loyalty in Fountain Park Apartment. The conclusion of this research is marketing mix (7P) consisting of product, price, promotion, place, people, process, and physicall enviroment simultaneously has a very significant impact on customer satisfaction in Fountain Park Apartment, and partially product, have negative significant effect on custumer satisfaction. Futhermore place, process, and physical environment have no significant effect on customer satisfaction in Fountain Park Apartment.